Molecular diagnosis and epidemiological aspects of cutaneous Leishmaniasis in Aleppo: Current status - Lana Kourieh; Mohammad Y. Abajy; Mahasen Alkebajy; Silva Ishkhanian; Ream Nayal (Parasite Epidemiology and Control)
For many decades, Cutaneous leishmaniasis (CL) has been endemic in Aleppo, Syria. The situation has worsened due to the ongoing war. Currently, CL diagnosis in Syria relies mainly on conventional methods, such as clinical symptoms and microscopic examination. This study aimed to evaluate the effectiveness of PCR (polymerase chain reaction) in diagnosing suspected CL cases. Two PCR protocols were applied: kDNA PCR for CL diagnosis and ITS2 PCR to identify the Leishmania parasite species. The results were compared with conventional methods, and correlations between CL prevalence and demographic factors were explored.Between January 2021 and October 2022, 105 suspected CL patients were screened at the Leishmania Center in Aleppo. kDNA PCR showed a sensitivity of 100 %, detecting positive results in 92 samples. Microscopic examination had a sensitivity of 76.1 %, identifying Leishmania amastigotes in 70 out of 92 samples. ITS2 PCR revealed that L. tropica was the dominant species (96.0 %) in Aleppo. Prevalence of CL was higher among men (54.3 %), the 13–25 years age group (39.1 %), and those with poor to moderate living conditions (87.0 %). Patients typically had an average of 3 lesions, with the upper extremities (55.4 %) and face (35.9 %) being the most affected areas. The study recommends using kDNA PCR for CL diagnosis due to its high sensitivity. Furthermore, the reported demographic and epidemiological data can inform public health authorities in their efforts to treat and prevent leishmaniasis in the country.